Ganoderma lucidum: A Source for Novel Bioactive Lectin - U. Girjal, Vinay; Neelagund, Shivayogeeswar; Krishnappa, Madappa (Protein and Peptide Letters, 2011)
Ganoderma lucidum is known for its high medicinal value, clinically used in treatment for various diseases. We have selected this mushroom for isolation of novel bioactive lectin. The isolation procedure comprised of ion-exchange chromatography on DEAE- cellulose and affinity chromatography on Affi-gel blue gel. Purified lectin was monomer with a molecular mass of 15 kDa, determined by SDS-PAGE, Gel filtration, MALDI-ToF. It showed hemagglutinating activity against both human and animal erythrocytes. The hemagglutination activity was not inhibited by simple sugars but inhibited by glycoproteins. The activity was maximal at pH range 4.0-9.0 and at temperature up to 60° C. The hemagglutination activity was stable even in the presence of 10mM EDTA and other divalent metal cations such as CaCl2, MgCl2, ZnCl2, and MnCl2. Lectin was shown antifungal activity against following pathogens Fusarium oxysporium, Penicillium chrysogenum, Aspergillus Niger, Colletotrichum musae, Botrytis cinerea, Trichophyton rubrum, Trichophyton tonsurans, Trichophyton interdigitale, Epidermophyton floccosum and Microsporum canis.
Keywords: lectin